Cross-sectional imaging combined with 3D-MR angiography (3D-MRA): diagnostic tool for preoperative vascular assessment of head and neck tumors - Sadick, Maliha; Sadick, Haneen; Hörmann, Karl; Düber, Christoph; Diehl, Steffen J. (Onkologie, 2005)
Background: Head and neck cancer accounts for 5% of all malignancies worldwide. The presence of lymph node metastases and vascular infiltration influence patient outcome. This prospective study describes the preoperative morphologic assessment of the vascular status of patients with head and neck tumors by means of high spatial resolution and extended coverage of the arterial and venous system reaching from the supra-aortic region to the skull base. Patients and Methods: Crosssectional imaging combined with contrast-enhanced 3Dmaximum intensity projection MR angiography (3DMRA) was applied using a dedicated head and neck coil with a 4-channel panorama array system interface to assess vascular involvement in patients with suspected head and neck cancer. 32 patients underwent preoperative assessment by magnetic resonance imaging (MRI). The results were then correlated with surgical and histological findings. Results: 3 of the 32 patients (9%) demonstrated involvement of the arterial system. In 2 of these 3 cases, MRA correctly predicted the arterial status, while in 1 case it gave a false negative result. 11 of the 32 patients (34%) presented with involvement of the venous system. 10 cases showed complete concordance between the findings of the MR venography and the intraoperative status, while in 1 case a false negative result was produced. Conclusion: In patients with suspected head and neck tumors, 3D-MRA in combination with cross sectional imaging is a valuable diagnostic tool for the detection of vascular involvement.